MOTIVASI TIM EKSTRAKURIKULER FUTSAL PUTRA SMK NEGERI 1 KEMLAGI MOJOKERTO - HADI MARUF, MOCHAMMAD; , PUDJIJUNIARTO (Jurnal Kesehatan Olahraga, 2019)
The State School 1 in carrying out extracurricular activities is very good so that there are several students taking part in some extracurricular activities, one of which is futsal, but there is one aspect that supports students in participating in futsal extracurricular activities namely motivation, namely the desire of someone who causes enthusiasm in doing an activity. This type of research uses quantitative descriptive, sampling in this study uses a total sampling technique that involves the entire population in the male futsal extracurricular team in the first Vocational School 1 Kemlagi in the amount of 12 people who are held in the field of 1 st public futsal in the next . the variable of this research is the level of motivation of the male extracurricular futsal in Vocational School 1 Kemlagi. The results of this study were the motivation of the male futsal extracurricular team at Vocational School 1 Kemlagi on intrinsic motivation of 83.7% while the motivation of extrinsic factors was 81.6% with the total average of both motivations of these factors amounting to 82.6% which included very high categories due to intrinsic motivation greater than extrinsic motivation shows that respondents are more dominant choosing intrinsic answers Keywords: Extracurricular, Motivation, FutsalSekolah Negeri 1 Kemlagi dalam menjalankan ekstrakurikulernya sangat baik sehingga terdapat beberapa siswa mengikuti beberapa ekstrakurikuler salah satunnya futsal, namun ada satu aspek yang mendukung siswa dalam mengikuti ekstrakurikuler futsal yaitu motivasi yaitu keinginan seseorang yang menimbulkan antusias dalam melakukan suatu aktivitas. Jenis penelitian ini menggunakan deskriptif kuantitatif, Pengambilan sampel dalam penelitian ini menggunakan teknik total sampling yaitu melibatkan seluruh populasi dalam tim esktrakurikuler futsal putra SMK Negeri 1 Kemlagi Mojokerto yang berjumlah 12 orang yang dilaksanakan dilapangan futsal SMK Negeri 1 Kemlagi. Variabel penelitian ini adalah tingkat motivasi tim ekstrakurikuler futsal putra SMK Negeri 1 Kemlagi. Hasil penelitian ini motivasi tim ekstrakurikuler futsal putra SMK Negeri 1 Kemlagi pada motivasi faktor intrinsik sebesar 83,7% sedangkan motivasi faktor ekstrinsik sebesar 81,6% dengan total rata-rata kedua motivasi faktor tersebut sebesar 82,6% yang termasuk kategori sangat tinggi dikarenakan motivasi intrinsik lebih besar dari pada motivasi ekstrinsik terlihat bahwa responden lebih dominan memilih jawaban intrinsik Kata Kunci : Ekstrakurikuler, Motivasi, Futsal